2020
DOI: 10.1177/1535759719895274
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy Benchmarks Area II: Prevent Epilepsy and Its Progression

Abstract: Area II of the 2014 Epilepsy Research Benchmarks aims to establish goals for preventing the development and progression of epilepsy. In this review, we will highlight key advances in Area II since the last summary of research progress and opportunities was published in 2016. We also highlight areas of investigation that began to develop before 2016 and in which additional progress has been made more recently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…However, the issue of developing an optimal method for stimulating neurotrophic factors and the safety of their use as therapeutic agents at the organismic level remains open. Thus, a number of studies have shown that an increase in the concentration of neurotrophic factors can provoke the development of seizure activity and disrupt the development of the vertebrate nervous system [ 22 ]. It was found that the neurotrophic factor BDNF has an excitatory effect on neuron cultures and brain slices of animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the issue of developing an optimal method for stimulating neurotrophic factors and the safety of their use as therapeutic agents at the organismic level remains open. Thus, a number of studies have shown that an increase in the concentration of neurotrophic factors can provoke the development of seizure activity and disrupt the development of the vertebrate nervous system [ 22 ]. It was found that the neurotrophic factor BDNF has an excitatory effect on neuron cultures and brain slices of animals.…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapy based on the use of viral vectors is considered the most promising option for the clinical application of neurotrophic factors BDNF and GDNF [ 20 ]. In particular, viral vectors are actively used in the therapy of various neuronal disorders and can be directly transduced into cells secreting neurotrophic factors [ 21 , 22 ]. Modern vectors provide stable, long-term gene expression, have an extensive spectrum of tropism for various organs and tissues, and also exhibit relatively low pathogenicity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 In general, ASM discovery and development are encouraged for orphan diseases (ie affecting <5/10 000 people in the general population), such as Dravet syndrome (DS). 6,7 This strategy has led to the discovery of fenfluramine (FA), a serotonergic drug, that successfully reduces seizures in DS patients. 8 This serotonergic drug is also under evaluation for other severe epilepsy syndromes, such as Lennox-Gastaut and Sunflower syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well-established that glial functions are commonly altered or disrupted in the process of epileptogenesis. Therefore, glial cells have come under recent focus as potential targets to promote homeostasis and functional recovery after a seizure or initiating epileptogenic event [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%